RNA-Seq uncovers endogenous NO-induced hormone signal transduction and carbon metabolism in response to PEG stress in alfalfa - Ying Zhao; Xiaofang Zhang; Yizhen Wang; Qian Ruan; Baoqiang Wang; Xiaoyue Wen; Xiaohong Wei (BMC Genomics)
Abstract Background Alfalfa (Medicago sativa L.) has the benefits of high yield and nutritional value as a sustainable forage. However, the water deficit significantly limits its growth and yield performance. Nitric oxide (NO) is a signal molecule that can enhance plant tolerance. The majority of previous studies focus on the role of exogenous NO in plant tolerance. However, the underlying mechanism of endogenous NO in alfalfa drought tolerance remains largely unexplored. Results To explore the mechanism of the endogenous NO-mediated water deficit resistance in the alfalfa, seedlings were exposed to polyethylene glycol 6000 (PEG) and NO scavenger (cPTIO). Results showed that PEG treatment significantly augmented alfalfa endogenous NO, MDA, O2 ·−, and H2O2 levels. In parallel, eliminating endogenous NO under PEG stress (PEG-NO) significantly diminished NO level, exacerbated MDA and reactive oxygen species accumulation, and decreased the activities of key enzymes involved in carbon fixation and TCA cycle, such as Rubisco, FBA, PDH, α-KGDH, and SDH, as well as reduced ABA and IAA content in alfalfa leaves. RNA-Seq and bioinformatics analysis suggested that endogenous NO-responsive DEGs primarily relate to carbon metabolism and hormone signal transduction. In further studies of these DEGs, we speculated that GH3, SAUR, SnRK2, and ABF genes and FBA, GAPDH, SBP, and CS are critical genes in response to endogenous NO under PEG stress. Conclusions In summary, our study innovatively proposes a mechanism model of how endogenous NO enhances alfalfa tolerance to water deficiency at the physiological and molecular levels. The novel candidate genes can give genetic resources for the subsequent molecular-assisted breeding of drought-resistant alfalfa crops.